2022
DOI: 10.1111/jvim.16530
|View full text |Cite
|
Sign up to set email alerts
|

Association of fecal and serummicroRNAprofiles with gastrointestinal cancer and chronic inflammatory enteropathy in dogs

Abstract: Background: Reliable biomarkers to differentiate gastrointestinal cancer (GIC) from chronic inflammatory enteropathy (CIE) in dogs are needed. Fecal and serum micro-RNAs (miRNAs) have been proposed as diagnostic and prognostic markers of GI disease in humans and dogs.Hypothesis/Objectives: Dogs with GIC have fecal and serum miRNA profiles that differ from those of dogs with CIE. Aims: (a) identify miRNAs that differentiate GIC from CIE, (b) use high-throughput reverse transcription quantitative real-time PCR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 112 publications
1
16
1
Order By: Relevance
“…In our study, serum miR‐223‐3p could distinguish between cats with GIC and CIE with an AUC of 0.90 (95% CI, 0.760‐1.0). A previous study reported similar performance with an AUC of 0.92 for this miRNA in feces for differentiating between GIC and CIE dogs 12 . MiR‐223‐3p was included in our study because it was previously found to be a potential fecal biomarker candidate for differentiation between GIC and CIE in dogs 12 .…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In our study, serum miR‐223‐3p could distinguish between cats with GIC and CIE with an AUC of 0.90 (95% CI, 0.760‐1.0). A previous study reported similar performance with an AUC of 0.92 for this miRNA in feces for differentiating between GIC and CIE dogs 12 . MiR‐223‐3p was included in our study because it was previously found to be a potential fecal biomarker candidate for differentiation between GIC and CIE in dogs 12 .…”
Section: Discussionmentioning
confidence: 77%
“…All healthy cats were recruited at UCPH. A study investigating miRNA in feces and serum from dogs using the same methodology has previously been published by this group 12 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Circulating miR-20b was described as a potential biomarker for distinguishing gastrointestinal cancer from chronic inflammatory enteropathy in dogs, which probably reflects the important role of miR-20b in intestinal diseases [ 18 ]. Decrease in miR-192 expression (together with the shift in other miRNAs) was described in the mucosa and serum of dogs with large intestinal inflammatory bowel disease [ 19 ].…”
Section: Introductionmentioning
confidence: 99%